Retrograde CT urethrography using a power injector quantitatively reveals effects of bladder distension on urethral size in healthy male Beagle dogs. Issue 3 (26th February 2020) - Kang, Kyuyong; Kim, Kyeonga; Oh, Donghyun; Choi, Jeongwoo; Choi, Mincheol; Yoon, Junghee
Abstract: Quantitative analysis of the normal retrograde urethrogram is well reported in radiography, but studies on CT urethrography are lacking. Recently, a method of retrograde CT urethrography using a power injector was described. The purpose of the current, prospective, analytical study was to quantify the urethral size of five, healthy, intact, male Beagle dogs using retrograde CT urethrography and a power injector. With the injection rate of the power injector set at 0.3 mL/s, 1 mL/kg of diluted contrast medium (15 mg I/mL) was injected, and a CT examination was performed. The state of the initial urethrogram taken was defined as "empty bladder." The same procedures were repeated with the injection of an additional 1 mL/kg of diluted contrast medium until the ureteral reflux was seen (distended bladder). There was a significant difference in volumes between the empty and distended bladder, but the membranous urethra showed the least difference ( P  = .0044) among the three regions ( P  < .0001 for the prostatic and penile urethra). Urethral diameters at six sites were measured from sagittal images, and the sites of measurements were adopted from the earlier radiographic studies. The most significant difference in the urethral diameters between the empty and distended bladder occurred at the cranial and middle prostatic urethra ( P  < .0001). The results of this study can be useful for interpreting the results of retrograde CT urethrography. Care must be taken when narrowing is suspected at the prostatic urethra, and if necessary, further distension of the urinary bladder should be tried.